Social media and digital communication during the pandemic - Platania, Federico; Toscano Hernandez, Celina (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2023)
During the first wave of COVID‑19, the uncertainty about a prospect vaccine combined with the constant media bombardment have fueled the fear of strict periods of confinement measures, creating a fertile ground for fake news and misleading social media debates. This paper studies how the public attention to certain pandemic-related topics and the social media activity of health and policymaker influencers impact the energy sector. Our findings suggest that during periods of growing attention to the term “Coronavirus”, social media activity of policymaker influencers exhibits a negative relationship with the energy sector. However, given the positive and scientific connotation, when the public attention to the term “Vaccine” increases, we observe a positive impact of international health organizations.